Type 2 Diabetes Mellitus and Pulmonary Tuberculosis: Literature Review of A Bidirectional Relationship - Liberty, Peggy; Liberty, Maggie (SCRIPTA SCORE Scientific Medical Journal, 2023)
ABSTRACT Background: Type 2 diabetes mellitus is a major health problem worldwide. In spite of the high incidence and prevalence, T2DM is often associated with pulmonary tuberculosis infection which is also a world health burden. T2DM is a chronic condition that suppresses immune system. T2DM increases 3 times the risk of pulmonary TB, increases the risk of pulmonary TB relapse, and causes higher mortality. Objectives: In this literature review, writers aimed to provide an overview of the relationship between T2DM and pulmonary TB including epidemiology, risk factor, pathogenesis, clinical manifestation, screening, treatment and prognosis.  Methods: This literature review is conducted by searching for articles using online search engine, including PubMed and Google Scholar. The selected articles include research articles, systematic reviews, meta-analyses and literature reviews published between 2015-2023 and are limited to those in English or Indonesian which are available in free full text. Discussion: T2DM is a risk factor for the occurrence of pulmonary TB. It also increases the severity of disease, incidence of relapse and MDR-TB. On the other hand, pulmonary TB worsening uncontrolled T2DM. Treatment of both T2DM and pulmonary TB must be adjusted if the two diseases co-occur. Mortality of pulmonary TB patients with T2DM is higher than pulmonary TB without T2DM. Conclusion:  T2DM and pulmonary TB are correlated to each other, having a bidirectional relationship. Keywords: diabetes mellitus, literature review, literature searching, pulmonary tuberculosis   ABSTRAK Latar Belakang: Diabetes melitus tipe 2 merupakan masalah kesehatan dunia. Selain kasusnya yang tinggi, DM tipe 2 sering kali dikorelasikan dengan kejadian infeksi tuberkulosis paru yang juga merupakan beban dalam kesehatan dunia. DM tipe 2 adalah penyakit bersifat kronis yang dapat melemahkan sistem kekebalan tubuh. Hal ini dapat meningkatkan risiko terjadinya infeksi TB paru 3 kali lebih besar dibandingkan non-DM, meningkatkan risiko reaktivasi TB paru serta menyebabkan mortalitas yang lebih tinggi. Tujuan: Kajian literatur ini bertujuan untuk membahas dan merangkum berbagai literatur terkait hubungan DM tipe 2 dan TB paru yang meliputi epidemiologi, faktor risiko, patogenesis, manifestasi klinis, skrining, pengobatan, dan prognosis, guna meingkatkan pengetahuan mengenai hubungan DM tipe 2 dan TB paru. Metode: Kajian literatur ini disusun dengan pencarian literatur dari PubMed dan Google Scholar. Artikel yang dipilih meliputi artikel penelitian, systematic review, meta-analysis, dan kajian literatur. Pencarian artikel terbatas pada publikasi berbahasa Inggris dan Indonesia yang tersedia dalam bentuk free full text dengan tahun publikasi 2015-2023. Pembahasan: DM tipe 2 menjadi faktor risiko untuk terjadinya TB paru, meningkatkan keparahan penyakit TB paru, meningkatkan risiko relaps serta kejadian MDR TB. Sebaliknya, TB paru menyebabkan DM tipe 2 menjadi sulit terkontrol.  Pengobatan DM tipe 2 dan TB paru harus disesuaikan jika kedua penyakit tersebut terjadi bersamaan. Mortalitas pasien TB paru meningkat pada kondisi DM tipe 2. Kesimpulan: DM tipe 2 dan TB paru saling mempengaruhi satu sama lain sehingga memiliki hubungan yang timbal balik. Kata Kunci: diabetes melitus, kajian literatur, pencarian literatur, tuberkulosis paru